PENGARUH KEADILAN ORGANISASIONAL TERHADAP KOMITMEN ORGANISASIONAL YANG DIMEDIASI KEPUASAN KERJA KARYAWAN DI CHILDFUND TIMOR LESTE - Soares Cabral, Jesuina; Sri Suprapti, Ni Wayan (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.07.TAHUN 2017, 2017)
Organizational commitment of employees is very important for an organization to achieve the goals that have been set. This study aims to 1) analyze the effect of organizational justice on employee job satisfaction. 2) To analyze job satisfaction on organizational commitment employee commitment. 3) To analyze the effect of organizational justice on employee job satisfaction. The population in this study is total employees working in organizational ChildFund Timor Leste. Based on existing data and the number of employees of the total amount is as much as 58 people. Consisting of employees of International and local employees. To answer the problem of research and test research hypotheses, used path analysis techniques. Managerial implications of this research are ChildFund East Timor can do more in-depth study, if conducted related changes in exchange. In addition, the organization must maintain aspects of procedural justice and interactional as both play a role in shaping employee satisfaction. The advice given is ChildFund East Timor should convince the employee that remuneration policies are applied solely to respect the competence of employees. In addition, organizations are expected to consistently apply justice mechanism that evenly felt by all employees both from a low position up to the highest position. Commitment organizations to pay attention to the satisfaction of all members of the field work.